2020
DOI: 10.1088/1361-6668/aba34e
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity of REBCO tapes in overcritical current regime: impact on superconducting fault current limiter modeling

Abstract: A detailed knowledge of the resistivity of high-temperature superconductors in the overcritical current regime is important to achieve reliable numerical simulations of applications such as superconducting fault current limiters. We have previously shown that the combination of fast pulsed current measurements and finite element analysis allows accounting for heating effects occurring during the current pulses. We demonstrated that it is possible to retrieve the correct current and temperature dependence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
18
2
Order By: Relevance
“…The first step requires a good initial guess of the involved quantities (namely h Ag and ρ Ag (T )). This is done by combining the characteristics provided by the manufacturer on the data-sheet with direct measurements of R vs T (carried out with an experimental setup similar to that described in [9]). The injected current to measure R vs T is very small (100 mA), and we can assume that the acquired voltage signal is given by the silver layer only.…”
Section: Optimization Method: Results and Discussionmentioning
confidence: 99%
“…The first step requires a good initial guess of the involved quantities (namely h Ag and ρ Ag (T )). This is done by combining the characteristics provided by the manufacturer on the data-sheet with direct measurements of R vs T (carried out with an experimental setup similar to that described in [9]). The injected current to measure R vs T is very small (100 mA), and we can assume that the acquired voltage signal is given by the silver layer only.…”
Section: Optimization Method: Results and Discussionmentioning
confidence: 99%
“…Previous studies have reported simulation methods for SFCL using Matlab/Simulink [23,24] and finite element method in COMSOL [18,21,25,26]. In this paper, a multilayer electrothermal coupled simulation model was built in MATLAB ® /Simulink to study the electrical and thermal behavior of the SFCL coil during quench [17,18,27,28]. Two stainless steel (SS) layers, silver layer, superconducting layer, and substrate NiW layer were considered in the model.…”
Section: Methodsmentioning
confidence: 99%
“…There are a lot of studies on the current limiting and recovery characteristics of coated superconductors and resistive SFCLs, by the means of experiment and numerical modelling [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations